Pelaksanaan Pembelajaran Seni Budaya (Musik) di Kelas VIII.2 SMPN 3 Sungai Geringging - Fajar Friatma; Syeilendra Syeilendra (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The purpose of this study was to describe the implementation of learning arts and culture (music) in class VIII.2 at SMP Negeri 3 Sungai Geringging. Researchers used qualitative research that is descriptive. The main instrument in this study was the researcher himself observing the learning process for class VIII.2 on the subject matter of music at SMP Negeri 3 Sungai Geringging. The type of data used is primary and secondary data. Data collection techniques were carried out by means of literature study, observation, interviews, and documentation. The steps to analyze the data are data collection, data reduction, data presentation, and drawing conclusions. The results of the study concluded that the process of implementing art and culture learning for music material in class VIII.2 had not gone well. This is because there are obstacles in which there are no learning media, and there is no infrastructure for musical instruments, as well as practice rooms so the teacher does not teach in accordance with the existing syllabus and lesson plan (RPP). Learning the art of music in class VIII.2 is one of them only fulfilling the core competency indicators in the syllabus, namely "understanding" traditional musical instrument material. Then the problems that occur in the class are the visible attitudes of students when participating in learning the art of music, students look bored and bored participating in learning traditional musical instruments, then there are some students who are seen often having permission to go in and out of class, chatting with their peers, ignoring the material provided teachers, so that they do not respond well to learning. Based on the results that have been concluded by researchers, students feel bored, experience boredom, and do not respond well to the material taught by the teacher, because learning the art of music is mostly done in theory only, while practice is never carried out and taught to students because there is no infrastructure. -musical instruments available, and a room for practicing musical art. In the teaching and learning process, there is no learning media available, then the methods taught by the teacher do not vary, the teacher more often uses the lecture and question and answer method only. So that in reality the learning objectives that must be achieved in the teaching materials owned by the teacher have not been achieved optimally.